Colloidal model for epitaxial growth in one dimension (2024)
Through a one-dimensional colloidal model for epitaxial growth, we characterize the nucleation and aggregation processes occurring in a gap between adjacent islands. The timescales associated with deposition, diffusion, aggregation, and nucleation inside the gap are studied in terms of the parameters defining the interaction between colloidal particles. Numerical results from molecular dynamics (MD) simulations are compared with those from analytical models, and good agreement between both data sets is found. The analytical and numerical results for the timescales are used to calculate the associated rates to generate kinetic Monte Carlo (kMC) simulations, which allow exploring larger systems and longer timescales in comparison with MD simulations. The kMC simulations reproduce the global behavior of the densities of islands and monomers and the gap length distribution between adjacent islands.